Four days of simulated shift work reduces insulin sensitivity in humans. (12th February 2018) - Bescos, R.; Boden, M. J.; Jackson, M. L.; Trewin, A. J.; Marin, E. C.; Levinger, I.; Garnham, A.; Hiam, D. S.; Falcao‐Tebas, F.; Conte, F.; Owens, J. A.; Kennaway, D. J.; et al.
Abstract: Aim: The aim of this study was to investigate the effects of 4 consecutive simulated night shifts on glucose homeostasis, mitochondrial function and central and peripheral rhythmicities compared with a simulated day shift schedule. Methods: Seventeen healthy adults (8M:9F) matched for sleep, physical activity and dietary/fat intake participated in this study (night shift work n   =   9; day shift work n   =   8). Glucose tolerance and insulin sensitivity before and after 4 nights of shift work were measured by an intravenous glucose tolerance test and a hyperinsulinaemic euglycaemic clamp respectively. Muscles biopsies were obtained to determine insulin signalling and mitochondrial function. Central and peripheral rhythmicities were assessed by measuring salivary melatonin and expression of circadian genes from hair samples respectively. Results: Fasting plasma glucose increased (4.4 ± 0.1 vs. 4.6 ± 0.1 mmol L −1 ; P  = .001) and insulin sensitivity decreased (25 ± 7%, P  < .05) following the night shift, with no changes following the day shift. Night shift work had no effect on skeletal muscle protein expression (PGC1α, UCP3, TFAM and mitochondria Complex II‐V) or insulin‐stimulated pAkt Ser473, pTBC1D4Ser318 and pTBC1D4Thr642. Importantly, the metabolic changes after simulated night shifts occurred despite no changes in the timing of melatonin rhythmicity or hair follicle cell clock gene expression across the wake period ( Per3, Per1, Nr1d1 and Nr1d2 ). Conclusion: Only 4 days of simulated night shift work in healthy adults is sufficient to reduce insulin sensitivity which would be expected to increase the risk of T2D.